Overhead costs : some essays in economic analysis - Lewis, W. Arthur (London : G. Allen & Unwin, 1949)
The book contained seven chapters and each chapter deals with problems that emanate with overhead costs.
Includes bibliographical footnotes and index.
rua 06/07/17
Loans
Keywords: Cost; Pricing; Monopolies